2016
DOI: 10.1186/s13256-015-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dental implant displaced into maxillary sinus by combination of endoscopically assisted and bone repositioning techniques: a case report

Abstract: BackgroundAccidental displacement of a dental implant into the maxillary sinus is an infrequent although not uncommon complication encountered in dental clinical practice, with the main cause thought to be inadequate bone height in the posterior maxilla. We report a case of migration of a dental implant into the maxillary sinus, and discuss the benefits of its removal by a combination of endoscopically assisted and bone repositioning techniques.Case presentationA 35-year-old Japanese man with a partially edent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 10 publications
0
51
0
Order By: Relevance
“…Methods used for foreign body removal differ according to the size and location of the foreign body (6). These include the AA, which enlarges the socket (19), the Caldwell-Luc approach, which opens the maxillary sinus from the canine fossa (19)(20)(21), and more recent methods using endoscopes (15,(22)(23)(24)(25). The AA is effective when the foreign body is in the lower part of the maxillary sinus and not perforating the mucous membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods used for foreign body removal differ according to the size and location of the foreign body (6). These include the AA, which enlarges the socket (19), the Caldwell-Luc approach, which opens the maxillary sinus from the canine fossa (19)(20)(21), and more recent methods using endoscopes (15,(22)(23)(24)(25). The AA is effective when the foreign body is in the lower part of the maxillary sinus and not perforating the mucous membrane.…”
Section: Discussionmentioning
confidence: 99%
“…3). Removal using endoscopy is classified into two categories: an approach from the nasal cavity or NE (24) and an approach from the oral cavity or OE (22,23,25). As the nasal approach is facilitated via the natural ostium, it is minimally invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the digital era of paperless journals with few space restrictions, the case report has seen a resurgence. The digital format facilitates searches, which is a key factor in their utility [7]. Most of the case report journals are open access and have high acceptance rates.…”
Section: Introductionmentioning
confidence: 99%
“…The case report about the use of FOLFIRI for UC by Lu et al . showed that UTUC was well controlled by the chemotherapy regimen, and, that it was effective for metastatic colorectal cancer [12]. There are few reports of FOLFOX therapy for UC, with only a phase II trial by Lorenzo et al .…”
Section: Discussionmentioning
confidence: 99%